Women’s collective action and sustainable water management: case of SEWA’s water campaign in Gujarat, India - Panda, Smita Mishra (International Food Policy Research Institute, 2006)
This paper discusses the case of the Self Employed Women’s Association’s (SEWA) Women, Water and Work Campaign which began in 1995 in the semi-arid regions of Gujarat. SEWA’s women’s groups, which are initiated through collective action, have been active in sustaining local water management through water harvesting, watershed management, handpump repair, pipeline maintenance and revival of traditional sources of water. Some of the significant factors that have sustained collective action of women are the presence of strong grassroots institution (pani samiti), the establishment of a technical cadre of women (barefoot technicians), the ability of women’s groups to transcend social barriers and continuous dialoguing with the state. The impact of collective action is far reaching both for SEWA as well as the women it serves. SEWA’s membership has increased manifold due to the success of the water campaign. Women have benefited in terms of increased income, reduced drudgery, improvements in the livelihoods of their families, reduced migration of both women and men and increased participation in SEWA’s other programs. The most important impact observed is the strengthening of women’s collective agency and women’s confidence to independently negotiate in the public domain in the water management sector, which was earlier occupied by men. Women’s collective agency has catalyzed some gender-equitable change processes, although perceptible changes in gender relations at the household level are not as significant. Some policy implications are discussed in terms of involving women at all levels of water management programs – planning, designing, implementing as well as monitoring.